(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes modern pedagogical approaches to organizing students’ independent learning activities and the theoretical foundations for developing independent learning competence. The motivational, cognitive, activity-based, and reflective components of independent learning competence are described, and their integration is substantiated as an important factor ensuring the effectiveness of students’ independent learning. In addition, the specific features of organizing students’ independent learning activities within the credit-module system and the pedagogical opportunities of the digital learning environment are examined. The article analyzes the significance of distance learning, adaptive learning, blended learning, and electronic educational resources in developing students’ independent learning, self-management, and reflective activity skills. Based on the scientific views of foreign, CIS, and local scholars, pedagogical mechanisms for the effective organization of independent learning are highlighted.